Teacher learning under co-construction: Affordances of digital social annotated reading - Kristen Michelson; Beatrice Dupuy (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Following calls for more extensive professional development (PD) opportunities for novice L2 teaching assistants (TA), this article reports on a PD activity implemented with six French TAs who read and discussed scholarly literature related to multiliteracies pedagogies through a digital social annotated reading (DSAR) platform in a discussion section concurrent to their methods course. Using the Community of Inquiry (CoI) framework developed by Garrison et al. (2000), participants' margin dialogues around academic articles were analyzed for indicators of cognitive, social, and teaching presence in order to examine the type and quality of knowledge co-construction that could emerge within this community of TAs. Findings reveal notably high levels of cognitive presence with respect to social and teaching presence, and compared to prior studies examining cognitive presence in more traditional types of digitally mediated discussion environments, such as discussion forums.